Pemisahan Pertanggungjawaban Perampasan Barang dalam Penguasaan Pihak Ketiga yang Beritikad Baik dalam Putusan Tindak Pidana Korupsi - Umara, Nanda Sahputra (Faculty of Law, University of Ahmad Dahlan, 2017)
Considering the development of modus operandi on crime of corruption, the quality of law enforcement in eradicating corruption needs to be increased. Many people are violated his rights over the lack of the duty and the responsibility of law enforcer. As in the verdict no. 42 / Pid.B / TPK / 2012 / PN.JKT.PST. Whereas in this verdict the judge shall also impose a crime in the form of the appropriation of certain goods against a good faithful third party, whereas confiscation is an additional criminal sanction under Article 10 of the Criminal Code and Article 18 of Law Number 31 Year 1999 jo. Law Number 20 Year 2001 on the Eradication of Corruption. In the criminal law conception criminal liability can only be charged to a person who has previously committed a crime. that in this Decision, according to the judge, the author has mistakenly applied the law to a good third party. should the seizure of a third party in this decision not be imposed through the criminal justice system but with other legal mechanisms outside the penal law both civil and administrative, because in principle the accountability in criminal law is based on in personam mechanism, therefore need to be separated from the concept of responsibility in the seizure of goods in the possession of a well-intentioned third party.